Komunitas Epistemik dalam Kebijakan Luar Negeri: Peran INACA dalam ASEAN Open Sky - Auva Syiahnaz Rizky Shafira; Mohamad Rosyidin; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The implementation of infrastructure development in ASEAN economic cooperation in the realm of air and maritime transportation is the cornerstone of the establishment of the ASEAN Open Sky. In every policy-making, Indonesia opens access for interest groups, including the epistemic community who want to exert influence in foreign policy. The epistemic community is a network of professionals with recognized expertise and has the authority to propose or make policies on certain issues that are relevant to their knowledge. The objective of this research is to explain the role of the epistemic community in the making and implementation of foreign policy, in this case INACA in ASEAN Open Sky using constructivism theory. According to constructivism, epistemic communities have an important role in policy making and implementation, they can help to shape the interests and preferences of the state. This research uses the qualitative method and the data needed is obtained through primary and secondary resources by interviewing relevant organizations and reviewing relevant literatures, such as books, journals, news, and another online sources. The interview method was carried out online through questionnaires. This research shows that the role of the epistemic community in policy making is less significant caused by the domination of the government and lack of support for the research development process by the epistemic community.